2020
DOI: 10.1002/jcla.23420
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between paramagnetic and CD71 magnetic activated cell sorting of fetal nucleated red blood cells from the maternal blood

Abstract: Background Fetal nucleated red blood cells (NRBC) from maternal circulation are rare events but can be enriched and used to evaluate the genetics of the fetus. We compared two simplified selection methods of the fetal cells from the maternal blood. Methods We isolated fetal cells from maternal blood through double‐density gradient centrifugation followed either by magnetic cell selection, based on the paramagnetic proprieties of the NRBC hemoglobin, converted to methemoglobin, or by a positive magnetic‐activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 33 publications
3
16
0
Order By: Relevance
“…The frequencies of those cells per milliliter of blood ranged from 0 to 1.7 (median 0.3). This median value was consistent with the average number of male (XY) NRBC cells in maternal blood isolated by CD71 antibody selection and identified by FISH (3.38 +/− 1.7 cells from 10 ml of blood), recently reported by Nemescu et al 16 …”
Section: Discussionsupporting
confidence: 91%
“…The frequencies of those cells per milliliter of blood ranged from 0 to 1.7 (median 0.3). This median value was consistent with the average number of male (XY) NRBC cells in maternal blood isolated by CD71 antibody selection and identified by FISH (3.38 +/− 1.7 cells from 10 ml of blood), recently reported by Nemescu et al 16 …”
Section: Discussionsupporting
confidence: 91%
“… 25 , 26 Both studies reported full accuracy in detected Y chromosome in the enrichment fNRBC as like the present study using double enrichment process. 17 …”
Section: Discussionmentioning
confidence: 99%
“…As a simple, fast, and economical bench-top technique with the capability to process large cell numbers, MACS is usually selected as a further enrichment method 46 . Transferrin receptor (CD71) is a common positive marker 47,48 , which was expressed on the entire erythroid lineage, activated lymphocytes, monocytes, trophoblasts, any cell incorporating iron and definitive fNRBCs in maternal and cord blood. In our study, DGC and MACS (anti-CD71) method were used to separate f{Choolani, 2003 #119}{Ganshirt, 1998 #69}NRBCs from maternal cord blood.…”
Section: Discussionmentioning
confidence: 99%